Achieving Learning Outcomes in the World of COVID - Jeffrey Ward; Frederick Burrack (Academic Chairpersons Conference Proceedings, 2022)
Presenters assessment will explore how focusing on the learning outcomes guides faculty into determining best instructional practices in a remote/hybrid delivery method, illustrating examples of faculty shifting from traditional face-to-face teaching strategies to remote or hybrid teaching strategies, while achieving the same learning outcomes.
Keywords: Instruction; Assessment; Pedagogy; Pandemic; Technology